Sterol 27-Hydroxylase Deficiency as a Cause of Neonatal Cholestasis: Report of 2 Cases and Review of the Literature - Lipiński, Patryk; Klaudel-Dreszler, Maja; Ciara, Elzbieta; Jurkiewicz, Dorota; Płoski, Rafał; Cielecka-Kuszyk, Joanna; Socha, Piotr; Jankowska, Irena (Frontiers in Pediatrics, 2021)
Introduction: Inborn errors of primary bile acid (BA) synthesis are rare autosomal recessive disorders responsible for 1-2% of cases of neonatal cholestasis. Among them, cerebrotendinous xanthomatosis (CTX) is caused by mutations in the CYP27A1 gene resulting in the impairment of sterol 27-hydroxylase enzyme activity. Patients and methods: Here we present the study on two siblings with neonatal cholestasis diagnosed with sterol 27-hydroxylase deficiency. The clinical, biochemical, histological and molecular presentation at the time of diagnosis and detailed follow-up were described. An extensive overview of the literature regarding patients with sterol 27-hydroxylase deficiency presenting with neonatal cholestasis was also provided. Results: Patient 1 presented with cholestatic jaundice since 10 weeks of age and developed the end-stage liver disease requiring liver transplantation at 8 months of age but finally succumbed 3 years post-transplantation due to autoimmune hemolytic anemia and multiorgan failure development. Next-generation sequencing performed post mortem, revealed him to be homozygous for the known pathogenic splicing variant c.1184+1G>A in the CYP27A1 gene. Patient 2 (sibling) presented with cholestatic jaundice since the first day of life. Sanger sequencing of CYP27A1 revealed the same results. Chenodeoxycholic acid treatment was introduced just after diagnosis, at 4 months of age. Fourteen patients with sterol 27-hydroxylase deficiency presenting with neonatal cholestasis were reported in the literature, in most of them presenting as a self-limiting disease. Conclusions: An early recognition and treatment initiation in CTX is essential.